Exploring the pharmacological mechanisms of icaritin against nasopharyngeal carcinoma via network pharmacology and experimental validation - Liu, Minglu; Hu, Tong; Gou, Wenfeng; Chang, Huajie; Li, Yanli; Li, Yiliang; Zuo, Daiying; Hou, Wenbin; Jiao, Shunchang (Frontiers in Pharmacology, 2022)
Background: Icaritin is a natural product with a wide range of anti-tumor effects. However, its anti-tumor mechanism has not been thoroughly studied. This study examined the inhibitory effect of icaritin on nasopharyngeal cancer and its underlying mechanism using network pharmacology along with in vivo and in vitro experiments. Methods: MTT and clone formation assays were used to detect the effects of icaritin on the viability and proliferation of nasopharyngeal carcinoma cells, followed by the construction of a HONE1 xenograft tumor model to evaluate the anti-tumor efficacy of icaritin in vivo. A public database was used to predict prospective targets, built a protein-protein interaction (PPI) network, and analyze gene enrichment and biological processes. Based on network pharmacological data, cell cycle-related proteins were identified using western blotting. Besides, cell cycle distribution, apoptosis, and intracellular reactive oxygen species (ROS) generation were identified using flow cytometry. In addition, SA-β-Gal staining was performed to detect cellular senescence, and western blotting was performed to detect the expression of P53, P21, and other proteins to verify key signaling pathways. Results: Icaritin effectively inhibited the viability and proliferation of nasopharyngeal carcinoma cell lines and showed good anti-tumor activity against HONE1 nasopharyngeal carcinoma cells in vivo. Key protein targets, including AKT1, HSP90AA1, CDK4, CCND1, and EGFR, were screened using PPI network topology analysis. GO and KEGG analysis revealed that the cell cycle, p53 signaling, and cell senescence pathways may be the main regulatory pathways. Flow cytometry and western blot experiments showed that icaritin caused S-phase arrest and promoted an increase in ROS. SA-β-Gal staining showed that icaritin significantly induced cellular senescence, and western blotting showed that the expression of senescence-related proteins p53 and P21 increased significantly. Moreover, inhibition of ROS levels by N-Acetylcysteine (NAC) enhanced cell viability, reversed cellular senescence and reduced cellular senescence-associated protein expression. Conclusion: The results of network pharmacological analysis and in vivo and in vitro experiments showed that icaritin effectively inhibited the growth of nasopharyngeal carcinoma cells, promoted ROS production, induced cellular senescence, and inhibited tumor cells, which are related to the regulation of P53/P21 signal pathway.